Isolasi dan Identifikasi Khamir Selulolitik Dari Tanah Rizosfer Anggrek Puser Bumi (Pecteilis susannae L.) di Hutan Wonosadi Gunung Kidul DIY - Lady Diana; Titi Lasmini (Biogenesis: Jurnal Ilmiah Biologi, 2016)
P. susannae (L.) Raf. is terrestrial orchid grown on the floor of Wonosadi forest. They belong to endangered species of orchid. Those orchids have grown well on degraded leaf litter and surround the grass. So, these plant were interesting to be elucidated especially for their nutrient availability. The was investigate the possibility of yeast associated with terrestrial orchids and cooperate in the provision of nutrients. The research objective was to obtain cellulolytic yeast on soil of root system P. susannae (L.) Raf. The research began with rhizosphere soil sampling on orchids root system P. susannae (L.) Raf. in two place in Forest Wonosadi. Soil samples were analyzed in the laboratory of microbiology, including the determination of the population of cellulolytic yeast and yeast isolated from soil of root system P. susannae (L.). directly from root system using Carboxy methyl cellulose medium (CMC), incubated for 5 days. Colonies were counted for the determination of population growth. Yeast colonies were grown separately isolated as a single culture. Sorting trough growth experiments using a form of cellulose (cellulose microcrystalline, leaf litter and paper) was different. Isolates were grown on microcrystalline cellulose selected for further testing based on the ability to use CMC. Activity was determined by the use of cellulose determine reducing sugar levels (glucose) was released using a spectrophotometer (OD 540 nm). The results showed that the rhizosphere soil P. susannae (L.) Raf. containing a yeast population (17x102 CFU and 2.3 x 102 CFU) and was dominated by the four isolates (K2, K16, A9 and A10) cellulolytic yeasts. The results of the identification of the four isolated of yeasts like Saccharomyces sp. (K2) and Candida sp. (K16, A9 and A10).